Penerapan Pendekatan Pembelajaran Konstruktivistik Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Kerja Bengkel Dan Gambar Teknik - Abdul Kadir (Journal of Classroom Action Research, 2023)
This study aims to describe the technical implementation of the constructivist learning model of the learning cycle, and to determine the increase in student achievement and activeness in the subject of Workshop Work and Engineering Drawings for class X Electronics Engineering Skills Competency at SMK Negeri 3 Mataram. This research is a Classroom Action Research (CAR). The subjects of this research were 32 students of grade X Electronic Engineering Skills Competency Even Semester at SMK Negeri 3 Mataram. Meanwhile, the object of this research is the study of Workshop Work and Technical Drawing subjects using constructivist learning methods. Data collection uses observation and test techniques with two cycle stages. Based on the results of the study it was concluded that: (1) the implementation of the implementation of the constructivist learning model of this learning cycle, namely in each cycle consists of planning, action, observation, and reflection. (2) The application of learning using the constructivist learning method can improve student achievement in class X of the Electronic Engineering Skills Competency Even Semester at SMK Negeri 3 Mataram. This is evidenced by the increase in student learning outcomes for each cycle, namely the average value of cycle I was 71 and cycle II was 79. Besides that, besides increasing the value of learning outcomes, students' positive activity also increased. It can be seen from each cycle of positive student activity increased from cycle I by 72% to 88% in cycle II. Learning is also more effective when it is shown that students quickly adapt from quite active learning to very active learning